The Influence of Love for Work, Servant Leadership, and Perceived Organizational Support in the Happiness Level among Muhammadiyah Teachers - Aulia, Aulia; Diawita, Milenia; Riska, Ahmad; Elisa, Lia; Wafa, Zaenal (Universitas Muhammadiyah Yogyakarta, 2024)
Happiness is important in maintaining the stability of human resources, including in the educational sector. However, studies on happiness at work are still neglected. In the organizational scale, the discussion on happiness is compelling as it relates to work achievement or productivity. Moreover, studies on factors affecting happiness at work are still limited, especially in teachers who work under the auspices of Muhammadiyah. The present study determines the influence of work passion, servant leadership, and perceived organizational support on teachers' levels of happiness in the workplace. The study used quantitative research with a correlation method. The research population is the teachers of 54 Muhammadiyah schools in Yogyakarta. The sample was determined using proportional cluster random sampling with 28 schools and 263 teachers. The instruments evaluated were work passion (α=0.975), servant leadership (α=0.952), perceived organizational support (α=0.869), and happiness at work scales (α=0.877). The data were analyzed using multiple regression analysis. The results showed that work passion, perceived organizational support, and servant leadership influence Muhammadiyah teachers' happiness at work in Yogyakarta. The teachers' personal factors (work passion) and organizational factors (principal leadership style) at work are essential to pay attention to in order to increase teachers' happiness.